Association between dermoscopic and reflectance confocal microscopy features of cutaneous melanoma with BRAF mutational status. (14th November 2016) - Bombonato, C.; Ribero, S.; Pozzobon, F.C.; Puig‐Butille, J.A.; Badenas, C.; Carrera, C.; Malvehy, J.; Moscarella, E.; Lallas, A.; Piana, S.; Puig, S.; Argenziano, G.; et al.
Abstract: Background: Melanomas harbouring common genetic mutations might share certain morphological features detectable with dermoscopy and reflectance confocal microscopy. BRAF mutational status is crucial for the management of metastatic melanoma. Objectives: To correlate the dermoscopic characteristics of primary cutaneous melanomas with BRAF mutational status. Furthermore, a subset of tumours has also been analysed for the presence of possible confocal features that might be linked with BRAF status. Methods: Retrospectively acquired dermoscopic and confocal images of patients with melanoma in tertiary referral academic centres: Skin Cancer Unit in Reggio Emilia and at the Melanoma Unit in Barcelona. Kruskal–Wallis test, logistic regressions, univariate and multivariate analyses have been performed to find dermoscopic and confocal features significantly correlated with BRAF mutational status. Results: Dermoscopically, the presence of irregular peripheral streaks and ulceration were positive predictors of BRAF ‐mutated melanomas with a statistically significance value, while dotted vessels were more represented in wild‐type melanomas. None of the evaluated reflectance confocal microscopy features were correlated with genetic profiling. Conclusions: Ulceration and irregular peripheral streaks represent dermoscopic feature indicative for BRAF ‐mutated melanoma, while dotted vessels are suggestive for wild‐type melanoma.